Vortex phase diagram and temperature-dependent second-peak effect in overdoped Bi2Sr2CuO6+δ crystals - Piriou, A.; Giannini, E.; Fasano, Y.; Senatore, C.; Fischer, O.; Fasano, Yanina (American Physical Society, 2010)
Fil: Fasano, Y. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; University of Geneve; Suiza